Effects of Milk Feeding Strategies on Short- and Long-term Productivity of Holstein Cows - M. Garcia; S. R. Montgomery; L. Hulbert; B. Bradford (Kansas Agricultural Experiment Station Research Reports, 2017)
The objectives of this study were to determine the impacts of feeding preweaning heifers with a high protein milk replacer (MR) or a raw or pasteurized non-saleable milk (NSM) on preweaning and first lactation performance. Holstein heifers (n = 154) were blocked by birth date and weight (BW) and within block randomly assigned to 1 of 3 treatments: 1) MR (4% protein and 2.6% fat, liquid basis); 2) pasteurized NSM (PNSM, 3.6% protein and 4.1% fat, liquid basis); or 3) raw NSM (RNSM, 3.6% protein and 4.1% fat, liquid basis). Heifers in RNSM were fed raw colostrum whereas heifers in MR and PNSM were fed pasteurized colostrum. Heifers were fed milk treatments 3 times per day. Low BW heifers (<80 lb) were fed 3 pints/feeding until the target BW was achieved (then 4 pints/feeding), whereas high BW heifers (≥ 80 lb) were fed 4 pints/feeding since birth. After weaning (≥ 42 d of age and consuming at least 2 lb grain mix for 3 consecutive days), all heifers were uniformly managed. Heifers fed MR instead of NSM ate less grain (0.76 vs. 0.95 lb/d, P = 0.01). Low BW heifers fed RNSM had lesser average daily gain than high BW heifers fed RNSM (P = 0.01) but daily gain did not differ among heifers fed PNSM, perhaps because low BW heifers consumed more grain than high BW heifers on this treatment (P = 0.01). The 305-day mature equivalent (ME) milk yield was lower for low BW heifers compared with high BW heifers, but only when fed RNSM (28,785 vs. 32,542 lb ME milk, P = 0.04). Similarly, ME fat yield was reduced when RNSM was fed to low-BW heifers (1,094 vs. 1,244 lb ME fat, P = 0.05). The type and quantity of milk fed did not impact reproductive efficiency (P>0.10). Feeding RNSM may impair the first lactation performance of low BW heifers, whereas it did not appear to affect high BW heifers.
Keywords: Heifers; milk replacer; pasteurization; life-long performance